7TM X-ray structures for class C GPCRs as new drug-discovery tools. 1. mGluR5. Issue 2 (15th January 2016) - Topiol, Sid; Sabio, Michael
Graphical abstract: Abstract: We illustrate, with a focus on mGluR5, how the recently published, first X-ray structures of mGluR 7TM domains, specifically those of mGluR1 and mGluR5 complexed with negative allosteric modulators (NAMs), will begin to influence ligand- (e.g., drug- or sweetener-) discovery efforts involving class C GPCRs. With an extensive docking study allowing full ligand flexibility and full side chain flexibility of all residues in the ligand-binding cavity, we have predicted and analyzed the binding modes of a variety of structurally diverse mGluR5 NAM ligands, showing how the X-ray structures serve to effectively rationalize each ligand's binding characteristics. We demonstrated that the features that are inherent in our earlier overlay model are preserved in the protein structure-based docking models. We identified structurally diverse compounds, which potentially act as mGluR NAMs, and revealed binding-site differences by performing high-throughput docking using a database of approximately six million structures of commercially available compounds and the mGluR1 and mGluR5 X-ray structures. By comparing the 7TM domains of the mGluR5 and mGluR1 X-rays structures, we identified selectivity factors within group I of the mGluRs. Similarly, using homology models that we built for mGluR2 and mGluR4, we have identified the factors leading to the selectivity between group I and groups II and III for ligands occupying the deepest portion of the mGluR5 binding cavity. Finally, we have proposed a structure-based explanation of the pharmacological switching within a set of positive allosteric modulators (PAMs) and their corresponding, very close NAM analogs.